Towards a carbon neutral Vestmannaeyjar. Comparison of alternative fuels for backup district heating of Vestmannaeyjar. - Christian Michael Barrera 1994- (2023)
This paper explores alternative fuels for backup district heating boilers in the remote area of Vestmannaeyjar in Iceland which does not have a reliable energy source. Currently, dirty marine diesel oil is used for backup energy generation, but emissions are high, sparking the need for cleaner alternatives as our planet faces a rapidly changing climate. This research has further implications worldwide in areas without reliable access to clean energy. Literature was reviewed for relevant biofuels and e-fuels, and six alternative fuels were chosen for investigation: hydrogen, methanol, bioethanol, methane, biodiesel, and ammonia. Data regarding environmental impact, thermofluid application, cost, availability, and storage and transportation was gathered for each fuel to fit an Analytical Hierarchy Process (AHP) model to make an informed decision given a complex decision matrix. With the scenario in Vestmannaeyjar, our AHP analysis showed e-methanol to be the most ideal fuel, with hydrogen coming in 2nd place and bioethanol coming in 3rd place for recommendation. The highest emphasis was placed on environmental impact given the purpose of this research. This paper concludes that e-methanol should be used for the backup district heating, but suggests some further research be done to also satisfy nearby industries using the same fuel source. Í þessari ritgerð eru mismunandi eldsneyti skoðuð fyrir notkun á varakatla fyrir hitaveitu Vestmannaeyja, sem hefur ekki áreiðanlegan orkugjafa. Í dag er notuð svartolía á varakatlana, en henni fylgir mikil losun og þörf er á hreinni valkostum. Sérstaklega í ljósi þess að jörðin okkar stendur frammi fyrir ört breytilegu loftslagi. Niðurstöður þessarar ritgerðar má nýta um allan heim á svæðum sem ekki hafa áreiðanlegan aðgang að hreinni orku. Skoðaðar voru ritrýndar heimildir um viðeigandi lífeldsneyti og rafeldsneyti og eftirfarandi sex önnur eldsneyti voru valin til rannsóknar: vetni, metanól, lífetanól, metan, lífdísill og ammoníak. Gögn um umhverfisáhrif, notkun hitavökva, ...